2002
DOI: 10.1152/japplphysiol.00949.2001
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxemia and low Crs in vagally denervated lambs result from reduced lung volume and not pulmonary edema

Abstract: Vagal denervation performed in the intrathoracic region in newborn lambs leads to hypoxemia and decreased respiratory system compliance (Crs), which could result from atelectasis and/or pulmonary edema. The objective of the present study was to quantify the relative roles of alveolar derecruitment and pulmonary edema as underlying cause(s) of respiratory failure. Vagal denervation was performed in the intrathoracic region and below the recurrent laryngeal nerves in six newborn lambs within 24 h of birth, where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…In a subsequent study, vagal denervation performed during the early postnatal period led to persistent hypoxaemia and apnoeas followed by respiratory failure within 24h post-denervation (Lalani et al 2001). Further investigations demonstrated that the mechanisms of respiratory failure included decreased functional residual capacity, attenuated expiratory braking, early suppression of augmented breaths, poor respiratory system compliance and atelectasis (Lalani et al 2001;Lalani et al 2002).…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…In a subsequent study, vagal denervation performed during the early postnatal period led to persistent hypoxaemia and apnoeas followed by respiratory failure within 24h post-denervation (Lalani et al 2001). Further investigations demonstrated that the mechanisms of respiratory failure included decreased functional residual capacity, attenuated expiratory braking, early suppression of augmented breaths, poor respiratory system compliance and atelectasis (Lalani et al 2001;Lalani et al 2002).…”
Section: Introductionmentioning
confidence: 95%
“…Establishment of pulmonary gas exchange is one of the most vital adaptations that must occur for the successful transition from fetal to neonatal life (Wong et al 1998;Greer et al 2006;Greer, 2012;Hooper et al 2015a;Hooper et al 2015b;Samson et al 2018). Evidence suggests that vagal innervation of the lung plays a critical role in establishing and maintaining adequate alveolar ventilation and pulmonary gas exchange during the early postnatal period (Fedorko et al 1988;Wong et al 1998;Harris & Milsom, 2001;Lalani et al 2001;Lalani et al 2002). However, the validity of some of these studies may have been compromised as a result of anaesthesia, possible secondary laryngeal obstruction and tracheostomy (Hasan et al 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, there are other sensors in the lungs and circulation whose inputs modify the behavior of the respiratory control system, including pulmonary stretch receptors, irritant receptors, and the "J" (juxta-capillary) receptors which may become important in disease states and which are discussed below. (26)(27)(28)(29)(30) The concept of loop gain…”
Section: Control Of Breathingmentioning
confidence: 99%
“…Finally, Paintal (33) discovered that nonmyelinated vagal fibers had sensory endings in the walls of alveoli that sense lung water. These afferents were subsequently shown to provoke rapid, shallow breathing and increase lung volume during pulmonary vascular congestion (34), and to play a vital role in newborns by preventing atelectasis and ensuring adequate alveolar ventilation (35).…”
Section: How Do We Generate Tidal Breathing?mentioning
confidence: 99%